2005
DOI: 10.1111/j.1475-097x.2005.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiation doses to staff involved in sentinel node operations for breast cancer

Abstract: The radiation exposure to the staff involved in sentinel node (SN) biopsy for breast cancer using radioactive labelled tracers will be considerably below the permissible limits, even with high numbers of SN biopsy procedures. Pregnant staff members should participate in <100 SN operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 27 publications
1
30
0
1
Order By: Relevance
“…A pregnant surgeon who participates in up to 100 SLN operations will stay below the limit of radiation exposure as recommended for pregnant women [135]. For a scrub nurse the exposure will be even less due to the larger distance from the source.…”
Section: Pregnant Staff In the Operating Roommentioning
confidence: 98%
See 1 more Smart Citation
“…A pregnant surgeon who participates in up to 100 SLN operations will stay below the limit of radiation exposure as recommended for pregnant women [135]. For a scrub nurse the exposure will be even less due to the larger distance from the source.…”
Section: Pregnant Staff In the Operating Roommentioning
confidence: 98%
“…Studies have demonstrated that the occupational doses are insignificant: the mean whole-body dose received by surgical staff has been measured at <1 μSv per operation [116,[133][134][135], with the maximum effective dose to the surgeons involved reported to be <2 μSv [34,116,136] . The radiation dose to the hands of the surgeon has been estimated to be 5 -94 μSv per patient [120].…”
Section: Staff In the Operating Roommentioning
confidence: 99%
“…Average exposure levels to the surgeon, anaesthetist, scrub nurses and operating room nurses were measured with digital dosimeters and reached up to 1 µSv/hour. According to published sources, the average exposure levels to operating-room staff were less than 1 µSv per one procedure during sentinel lymph node biopsy of patients with skin melanoma or breast cancer (9)(10)(11). The recommendations of the European Society of Nuclear Medicine state that the monitoring of operating room staff for professional exposure and additional measures of screening from ionizing radiation are not necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Enjeksiyon ile cerrahi arasındaki zaman arttıkça ekibin aldığı doz da azalmaktadır (16,17). Yıllık toplumun alabileceği doz limiti 1 mSv düşünüldüğünde bu radyasyon dozunun önemsenmeyecek seviyelerde olduğu söylenebilir.…”
Section: Sentinel Lenf Bezi Biyopsisi Dikkat Edilmesi Gerekenlerveuyaunclassified